Development of Socio-scientific Issues-Based Teaching Materials on Ecosystem Materials in Elementary School - Gayut Fatwa, Gayut; Aynin Mashfufah, Aynin Mashfufah; Mardhatillah, Mardhatillah (Journal of Learning Improvement and Lesson Study, 2025)
Abstract The use of social scientific issues that occur in the environment around students to be used as material content in learning makes learning more meaningful. These issues can be involved in learning through the Socio-scientific Issues framework. The existence of issues in around students that can be raised in learning, the author is interested in developing SSI-based teaching material integrated with HOTS. The research was conducted in three elementary schools, namely UPT SD Negeri Ngadirenggo 02, UPT SD Negeri Ngadirenggo 04, and UPT SD Negeri Ngadirenggo 05 which have similar backgrounds and environmental conditions. This research is R&D using the ADDIE model, but it is still limited to the development stage. This research, aims to produce a printed teaching material that is practical and effective to use. After the development process and validated by expert, this teaching material received the "very valid" category. Meanwhile, the results of small group trials, teaching materials are considered practical to use. Based on the validity and practicality test, this teaching material is declared eligible for research at the implementation stage.